Increased Non-locomotor Motion Through Instructional Leadership Method in Retarded Students in Special Schools Perwari Padang - Surohmat; Eko Purnomo; Eddy Marheni (International Conference of Mental Health, Neuroscience, and Cyber-psychology)
This study uses a qualitative method,with data collection methods using interviews and observations,The application of the researcher collects retarded children and then gives direction regarding the implementation of the correct heating movement which starts from head to foot. This research was conducted on July 20 - September 25 2018 at Padang Perwari Special School , West Sumatera.The informants in this study were teachers who taught at an extraordinary school in Padang Perwari which amounted to 3 people,with research subjects amounting to 30 mentally disabled students.In this research treatment,learning is done using the Instructional Leadership method.The researchers' preliminary findings indicate several problems regarding non-locomotor motion in mentally retarded children.Then the form of completion is given by using the Instructional Leadership method and the result is an increase and ease of student learning in carrying out non-locomotor movements.